Nutritional status, yield and composition of peach fruit subjected to the application of organic compost (Acta Scientiarum. Agronomy, 2016)
The purpose of this study was to evaluate the nutritional state, yield and composition of peaches on peach trees subjected to the application of organic compost to the soil. This experiment was conducted during the 2008 and 2009 cropping season in an orchard containing Chimarrita cultivars grafted onto Capdeboscq rootstocks and Haplumbrept soils in the municipality of Farroupilha (RS), Brazil. The treatments included 0, 9, 18, 36, 72 and 144 liters of organic compost per plant-1 year-1. The total nutrient contents in the leaves, yield components, yields per plant and hectare and compositions of the fruits were evaluated in 2008 and 2009 soon after harvest and after 30 days of storage. The application of organic compost to the soil increased the yield components and the yields per plant and hectare in the two treatments with the highest compost additions, which indicated that the addition of 72 L of compost per plant-1 is ideal economically. The organic compost had little effect on the composition of the peach fruit after harvest and after 30 days of storage.